Faktor-Faktor yang Berhubungan dengan Pencegahan Anemia pada Remaja Putri di SMA Negeri 4 Kota Jambi Tahun 2018 - Nurbaiti Nurbaiti (Universitas Batanghari Jambi, 2019)
Anemia is one of the health problems throughout the world, especially developing countries, which is estimated that 30% of the world's population suffer from anemia. Anemia often occurs in adolescents and pregnant women. Anemia in young women is still quite high, according to the World Health Organization (WHO 2013).This study aims to determine the relationship of knowledge, the role of the family, the role of health workers and information media with the prevention of anemia and can be used as information in SMAN 4 Kota Jambi.Anemia is a condition in which the reduction of red blood cells (erythrocytes) in the blood circulation or hemoglobin mass so that it is unable to fulfill its function as an oxygen carrier network.This research was conducted at SMAN 4 Kota Jambi, this research is a quantitative research using descriptive method and with proportional random sampling random sampling technique.The population in this study were all adolescents of class X and XI in SMAN 4 Jambi City totaling 826 people and the sample in this study were 124 students from SMAN 4 Kota Jambi.his research was conducted for one semester in 2018 and then analyzed by univariate, bivariate and multivariate. Based on the results of the bivariate analysis, it was found that there were 4 independent variables related to prevention of anemia in adolescent girls, namely knowledge (p-Value = 0.004), family role (p-Value = 0.021), role of health workers (p-Value 0.017), and media information (p-Value 0,000).The most dominant information media variable is related to pen preventionna nameia, the advice given to high schools to cooperate with the puskesmas to provide information to young women in SMAN 4 Jambi City regarding the prevention of anemia.